Precipitation reduction alters herbaceous community structure and composition in a savanna. (1st July 2019) - Jin, Yanqiang; Li, Jing; Liu, Chenggang; Liu, Yuntong; Zhang, Yiping; Song, Qinghai; Sha, Liqing; Balasubramanian, Durairaj; Chen, Aiguo; Yang, Daxin; Li, Peiguang
Abstract: Questions: In the changing climate scenario, the decline in precipitation is expected to alter water availability for plants, which in turn affects plant community structure and composition. The responses of community composition and structure to declines in precipitation are well documented in other biomes but remain understudied in water‐limited savannas. Location: A savanna ecosystem in southwest China. Methods: We used a four‐year (2014–2017) precipitation manipulation experiment to examine changes in herbaceous community composition and structure across the species, functional group and community levels under precipitation reduction. Results: Precipitation reduction significantly decreased the average height and percentage cover of the herbaceous community, while increasing species richness and the Pielou evenness index. Precipitation reduction significantly decreased average height, percentage cover and relative abundance of graminoids and perennials, but increased those of forbs and annuals. Precipitation reduction prompted a shift in the dominant species of the herbaceous community towards Fimbristylis monostachya . Conclusions: The results show that precipitation reduction changed the composition and structure of the herbaceous community of this savanna. Furthermore, they provide strong evidence that changes in herbaceous community structure and composition in response to the intensity and duration of precipitation reduction in this savanna exhibited relatively low thresholds, which suggests that the herbaceous community's response to a decline in precipitation was essentially nonlinear. These findings imply that even relatively small declines in precipitation may stimulate shifts in plant community structure and composition and affect the function and stability of savanna ecosystems. Abstract : We tested the responses of the herbaceous community's composition and structure across species, functional groups and community levels under precipitation reduction in a savanna. Herbaceous community structure and composition changes in response to the intensity and duration of precipitation reduction in this savanna exhibited relatively low thresholds, suggesting that the herbaceous community's response to a decline in precipitation was essentially nonlinear.